(untitled) (Research, Society and Development, 2022)
The investigation of soils shear strength is necessary in many Geotechnical Engineering applications, e.g. foundations, slope stability and retaining walls design. It is usually conducted by means of field and/or laboratory standard tests. In both cases, they are time-consuming and require specialized personnel to be performed. Several studies are found in the literature in which artificial intelligence tools are used as an alternative to those tests. This paper presents a systematic mapping review on this subject, in which algorithms types and geotechnical parameters needed to estimate soils shear strength are identified, based on data extracted from the literature. It was possible to list 17 techniques applied to different soil types. The results from these studies have been in good agreement with data from real laboratory and/or field tests. This demonstrates the potential of application of artificial intelligence to estimate soils shear strength.